2009
DOI: 10.1369/jhc.2009.952473
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Mucus Alterations Associated With MurineHelicobacterInfection

Abstract: The C57BL/6 mouse has been shown to develop gastric adenocarcinoma after Helicobacter felis infection. This model was used to determine whether mucin and trefoil factor (TFF) expression after infection was altered in a similar fashion to the changes seen in the protective gastric mucus layer of the human stomach after H. pylori infection. Our results indicate that this mouse model mimics many of the changes seen after human H. pylori infection, including increased expression of muc4 and muc5b and loss of muc5a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 70 publications
3
23
0
Order By: Relevance
“…S1C and D in the supplemental material). This mucin is normally not expressed in a healthy stomach (20). Compared to the results for the control animals, whose mRNA expression levels were set to 1, the fold differences in Muc5B and Muc5AC expression in the antrum were 6.02 Ϯ 2.27 for ASB1.4-and 5.68 Ϯ 2.81 for SS1-infected mice.…”
Section: Resultsmentioning
confidence: 94%
“…S1C and D in the supplemental material). This mucin is normally not expressed in a healthy stomach (20). Compared to the results for the control animals, whose mRNA expression levels were set to 1, the fold differences in Muc5B and Muc5AC expression in the antrum were 6.02 Ϯ 2.27 for ASB1.4-and 5.68 Ϯ 2.81 for SS1-infected mice.…”
Section: Resultsmentioning
confidence: 94%
“…Within the subset of H. pylori-infected individuals who do display gastric disease, clinical studies have revealed a gradual progression in disease severity over several decades (the Correa pathway) (8,26). The initial gastritis consists of both active (neutrophilic) and chronic (monocytic and lymphocytic) inflammation, which may be followed by gastric atrophy (loss of differentiated epithelia), intestinal metaplasia (altered mucin structure and expression), and dysplasia (abnormal cell growth and development) before stomach cancer (27). Approximately 10 -20% of infected subjects will develop gastric and duodenal ulcers, 1-2% will develop adenocarcinoma, and less than 1% will acquire gastric MALT lymphoma (28).…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that this observation was also true of H. felis-infected B6.ASF stomachs by immunofluorescence staining, as gastric glands had decreased zymogenic zone but unaltered antral zone protein expression of muc5ac after infection (data not shown). However, we were much more interested in the expression of muc4 and muc5b after infection, as our previous experiments have demonstrated that the alteration in gastric expression of these two mucins after H. felis infection only occurs if the adaptive immune response is intact (Schmitz et al 2009). Intriguingly, 8 weeks after infection, the expression of muc4 and muc5b is only increased in the B6.SPF model.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations include an increase in the gene expression of both muc4 and muc5b and a decrease in the protein expression of muc5ac. Although we have shown that these changes are dependent on the presence of an adaptive immune response, the effects of commensal microbiota are unknown (Schmitz et al 2009). To explore the role of gastric microbiota in these alterations in mucin expression, we first evaluated the levels of gene expression of four components of either normal gastric mucus or mucus found in H. felis-infected B6.SPF mice.…”
Section: Mucin Alterations Only Seen After H Felis Infection Of B6smentioning
confidence: 94%
See 1 more Smart Citation